Application of strategic self-talk: an experimental study on the effects on shooting stability and performance - Tzormpatzakis, E.; Galanis, E.; Chaldeaki, A.; Hatzigeorgiadis, A. (International Journal of Kinesiology & Sports Science, 2022)
Background: Pistol shooting is a sport with high attentional demands. Strategic self-talk has been shown to assist learning and increase performance, in particular due to its effects on attention. Objective: The current study aimed to examine the impact of a strategic self-talk intervention on the learning of pistol shooting. Methods: An experimental study was designed and implemented. Forty sport sciences students with no experience in pistol shooting were randomly assigned to experimental and control groups. The study took part in nine sessions, one for familiarization, two for baseline measurements, four for training, and two for final measurements. The shooting was performed from a distance of five meters and recorded through the SCATT shooting system. Performance as Average Score (AS) and two stability variables, Average Length of Tracing (ALOT) and Stability of Aim (SOA), were recorded. Results: Repeated measures MANOVA showed a significant multivariate group by measurement interaction. Pairwise comparisons revealed that (a) AS increased for both the experimental (p<.001) and the control group (p=.006), with the experimental group showing greater improvement, and (b) SOA and ALOT improved for the experimental group (p<.001 and p=.003, respectively) but not for the control group (p=.37 and p=.21, respectively). Conclusions: The increases in performance for both groups can be attributed to the learning effect; however, the impact of self-talk was evidenced in the greater performance improvement, but also in the improvement of the stability variables that were targeted through the instructional self-talk cues that were used. The greater performance change for the self-talk group may be attributed to attentional mechanisms that brought about the improvement of the stability parameters.